2015
DOI: 10.5028/jatm.v7i1.358
|View full text |Cite
|
Sign up to set email alerts
|

Nanoelectronic Devices Based on Carbon Nanotubes

Abstract: ABSTRACT:Carbon nanotubes are possible building blocks in the development of new generation of electronic devices. The carbon nanotubes allow one fabrication of devices using nanometric scales. They can be used in projects of a wide range of electronic and optoelectronic components such as diodes, transistors and interconnection elements, among others. This paper presents the state-of-the-art of this area, emphasizing the influence of quantum effects on the characteristics of such components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…CNTs are well-ordered, highaspect-ratio hollow graphite rods that were identified by Iijima in 1991 [33]. Since then, CNTs have been widely used in many areas, including electrode materials [34], nanoelectronics components [35], biosensors [36], strengthening of materials [37], and as components of biomaterials for drug delivery or other types of therapy [38][39][40][41]. The synthesis of CNTs is a broad topic and will not be described here in detail; however, it should be noted that the most used methods are electric-arc discharge [42], laser ablation [43], and the wide family of catalytic chemical vapor deposition (CCVD) methods [44].…”
Section: Properties Modifications and Application Of Cntsmentioning
confidence: 99%
“…CNTs are well-ordered, highaspect-ratio hollow graphite rods that were identified by Iijima in 1991 [33]. Since then, CNTs have been widely used in many areas, including electrode materials [34], nanoelectronics components [35], biosensors [36], strengthening of materials [37], and as components of biomaterials for drug delivery or other types of therapy [38][39][40][41]. The synthesis of CNTs is a broad topic and will not be described here in detail; however, it should be noted that the most used methods are electric-arc discharge [42], laser ablation [43], and the wide family of catalytic chemical vapor deposition (CCVD) methods [44].…”
Section: Properties Modifications and Application Of Cntsmentioning
confidence: 99%
“…Therefore, they are highly suitable for a number of applications, such as nano-optics, nanoelectronics, optoelectronics, and photovoltaics. [29][30][31] In particular, it was shown that CNTs could be used as interconnection elements, nanotransistors, detectors, light-emitting diodes, and transparent or opaque electrodes of solar cells. [32][33][34][35] In comparison to bulk materials, NTs show plasmon resonances associated with a slow surface wave propagating along their axis, which can be effectively controlled by the length of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from semiconductor devices, other nanoscale devices such as optoelectronics, electromechanical actuators/sensors, thermoelectric materials also face similar heat generation challenges, for example, nanotube-based electronics, , nanowire array-based lasers, , super lattice-based thin-film thermoelectric materials, , and nanowires. , The lack of thermal metrology at the nanoscale is a major impediment for scientific and economic developments.…”
mentioning
confidence: 99%